Persepsi dan Kepuasan Konsumen Pada Pembelian Kopi Nira Aren Di Pondok Kopi Aren Damai Langgeng Kota Pekanbaru - Evy Maharani; Nikita Salsabila; Yeni Kusumawaty (Jurnal Penelitian Pertanian Terapan, 2024)
This research aimed to understand customer characteristics, analyzed perception based on the level of importance dan performance of marketing mix attributes, and assesed consumer satiscfaction level with the marketing atribut of Pondok Kopi Aren Damai Langgeng in Pekanbaru City. The respondents were selected by purposive sampling method. Data were analyzed using descriptive analysis, Importance Performance Analysis (IPA) and the Customer Satisfaction Index (CSI) method. The research results indicated that the highest to lowest level of importance and performance of marketing mix variables, in sequence, are product, place, price and promotion. Meanwhile, in terms of performance, the sequence are product, price, place and promotion.The results showed the characteristic of consumers based on gender were dominated by men, with the age category “late adulthood” which is 36-45 years, married, has college education, with a job as a entrepreneur and average monthly income >IDR.4.500.000. Based on the Cartesian diagram analysis, the atribut that urgently need improvement are business sign, facilities and infrastructure. The results of the research showed that the Customer Satisfaction Index (CSI) is 79,32%, which indicates that customer satisfaction is within the category of satisfied.